Novel Antioxidant, Anti-α-Amylase, Anti-Inflammatory and Antinociceptive Water-Soluble Polysaccharides from the Aerial Part of Nitraria retusa - Rjeibi, Ilhem; Hentati, Faiez; Feriani, Anouar; Hfaiedh, Najla; Delattre, Cédric; Michaud, Philippe; Pierre, Guillaume (Foods, 2019)
In this paper, water-soluble polysaccharides (named as NRLP) were extracted from Nitraria retusa leaves. The main structural features of NRLP were determined by High-pressure size exclusion chromatography, Fourier transform infrared and Gas Chromatography/Mass Spectrometry-Electronic Impact analysis. The in vitro and in vivo biological potential of NRLP were evaluated by measuring its antioxidant (•OH and DPPH• scavenging, total antioxidant capacity), anti-α-amylase as well as anti-inflammatory and antinociceptive activities in a mice model. NRLP was composed of Rha (33.7%), Gal (18.1%), GalA (15.0%), Glc (13.3%), Ara (13.3%), Xyl (3.8%), and GlcA (2.8%) and showed a Molecular Weight (Mw) of 23.0 kDa and a polydispersity index (PDI) of 1.66. The investigations highlighted a significant antioxidant activity (IC50 = 2.4–2.6 mg/mL) and an inhibition activity against α-amylase (IC50 = 4.55 mg/mL) in a dose-dependent manner. Further, NRLP revealed interesting anti-edematous effects and antinociceptive activities (both > 70%). These results open up new pharmacological prospects for the water-soluble polysaccharides extracted from Nitraria retusa leaves.